2018
DOI: 10.1002/chem.201800674
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Photodynamic Activity of Lipid–Membrane‐Incorporated Fullerene Derivative by Combination with a Photo‐Antenna Molecule

Abstract: The weak absorbance of pristine C , C , and fullerene derivatives at wavelengths over 600 nm hampers the use of these molecules as photosensitizers (PSs) for photodynamic therapy (PDT). The coexistence of light-harvesting antenna molecules with a fullerene derivative in lipid membrane bilayers solved this issue. By controlling the location of the C derivative in the lipid membrane, the liposomal dyad system for PDT improved the photodynamic activity via an efficient photoenergy transfer from antenna molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…By controlling the location of the C 60 derivatives in the liposomes by using ap olar substituent, [113] the dyad system is expected to achieve efficient photoenergy transfer between the C 60 derivative andD iD and to improve the photoinduced cytotoxicity. [116] Compound 2 was therefore employed as the photoactive molecule. The fluorescence quenching effect of LMI2-DiD (87 %) was much higher than those of LMIC 60 -DiD and LMIC 70 -DiD (55 and 59 %, respectively); this indicated that energy transfer occurred more efficiently from photoactivated DiD to 2,t han that to C 60 or C 70 .I nc ontrast, the fluorescenceq uenching effects of DiD in aqueous solution were compared with the g-CDx·C 60 and g-CDx·2 complexes in the absence of liposomes.…”
Section: Photoinduced Cytotoxicityo Fliposome-incorporated Fullerenesmentioning
confidence: 71%
See 1 more Smart Citation
“…By controlling the location of the C 60 derivatives in the liposomes by using ap olar substituent, [113] the dyad system is expected to achieve efficient photoenergy transfer between the C 60 derivative andD iD and to improve the photoinduced cytotoxicity. [116] Compound 2 was therefore employed as the photoactive molecule. The fluorescence quenching effect of LMI2-DiD (87 %) was much higher than those of LMIC 60 -DiD and LMIC 70 -DiD (55 and 59 %, respectively); this indicated that energy transfer occurred more efficiently from photoactivated DiD to 2,t han that to C 60 or C 70 .I nc ontrast, the fluorescenceq uenching effects of DiD in aqueous solution were compared with the g-CDx·C 60 and g-CDx·2 complexes in the absence of liposomes.…”
Section: Photoinduced Cytotoxicityo Fliposome-incorporated Fullerenesmentioning
confidence: 71%
“…However, because C 60 , which exists near the center of the membrane bilayer, as mentioned in Section 3.4, keeps DiD at a distance, the positions are not optimal for energy transfer between C 60 and DiD. By controlling the location of the C 60 derivatives in the liposomes by using a polar substituent, the dyad system is expected to achieve efficient photoenergy transfer between the C 60 derivative and DiD and to improve the photoinduced cytotoxicity . Compound 2 was therefore employed as the photoactive molecule.…”
Section: Photoinduced Cytotoxicity Of Fullerenes Incorporated Into Somentioning
confidence: 99%
“…This work fully elaborates the capabilities of fullerene@protein complexes as image‐guided PDT agents. As such complexes are highly adaptable, future work could aim at their functionalization both with tumor‐targeting tags to improve the cancer cell selectivity and promote the cellular uptake of the photosensitizing agent, [ 76 ] and with light‐harvesting molecular antennae [ 45,77–79 ] to improve both therapeutic efficiency and treatment depth in PDT.…”
Section: Discussionmentioning
confidence: 99%
“…26 In particular, liposomal membranes are attractive platforms for designing and constructing assembled systems of fullerenes with dialkylated light-harvesting antenna molecules. [32][33][34] Previously, the poor absorption capacity of our photosensitizers over the longwavelength range between 600 and 700 nm was improved and the photoinduced cytotoxicity toward HeLa cells of these types of assembled systems was enhanced. Without the need for complicated synthesis of fullerenes, we used our system, which is based on LMI systems, to maximize and expand the availability of our photosensitizers at will by combining them with commercially available light-harvesting molecules.…”
mentioning
confidence: 97%
“…The preparation and detailed characterization of the catC 60 / light-harvesting antenna molecule assembled system integrated into the liposomal membranes are reported elsewhere. 33 Briey, LMI-light-harvesting antenna molecules were prepared via a conventional freeze-thaw method using DMPC and dyes such as 1,1 0 -dioctadecyl-3,3,3 0 ,3 0 -tetramethylindocarbocyanine perchlorate (DiI; l max , 549 nm) and 1,1 0 -dioctadecyl-3,3,3 0 ,3 0tetramethylindodicarbocyanine (DiD; l max , 644 nm). Aerward, the catC 60 was introduced into the liposomal membranes via an exchange reaction 33 by mixing the catC 60 /g-cyclodextrin complex at 80 C, a temperature which is higher than the phase transition temperature of DMPC (DMPC, 1 mM; DiD or DiI, 0.025 mM; catC 60 , 0.05 mM).…”
mentioning
confidence: 99%